Live imaging of wound angiogenesis reveals macrophage orchestrated vessel sprouting and regression. (4th June 2018) - Gurevich, David B; Severn, Charlotte E; Twomey, Catherine; Greenhough, Alexander; Cash, Jenna; Toye, Ashley M; Mellor, Harry; Martin, Paul
Abstract: Wound angiogenesis is an integral part of tissue repair and is impaired in many pathologies of healing. Here, we investigate the cellular interactions between innate immune cells and endothelial cells at wounds that drive neoangiogenic sprouting in real time and in vivo . Our studies in mouse and zebrafish wounds indicate that macrophages are drawn to wound blood vessels soon after injury and are intimately associated throughout the repair process and that macrophage ablation results in impaired neoangiogenesis. Macrophages also positively influence wound angiogenesis by driving resolution of anti‐angiogenic wound neutrophils. Experimental manipulation of the wound environment to specifically alter macrophage activation state dramatically influences subsequent blood vessel sprouting, with premature dampening of tumour necrosis factor‐α expression leading to impaired neoangiogenesis. Complementary human tissue culture studies indicate that inflammatory macrophages associate with endothelial cells and are sufficient to drive vessel sprouting via vascular endothelial growth factor signalling. Subsequently, macrophages also play a role in blood vessel regression during the resolution phase of wound repair, and their absence, or shifted activation state, impairs appropriate vessel clearance. Synopsis: Live imaging studies in zebrafish, alongside mouse and in vitro human cell studies reveal how macrophages play essential roles in wound angiogenesis, coordinating both the initial blood vessel sprouting and subsequent vessel regression. Pro‐inflammatory wound macrophages interact with blood vessel tips, driving sprouting angiogenesis at the wound site during early stages of repair by acting as a local source of vegf. Neutrophils are transient at the wound site where they suppress sprouting angiogenesis; they are subsequently dismissed from vessel tips by macrophages to establish an angiogenic "permissive" area. Anti‐inflammatory macrophages play a role in blood vessel regression and phagocytic clearance during wound resolution, and this function is impaired if macrophages remain pro‐inflammatory. Abstract : Imaging studies in zebrafish, mouse and human cells reveal how macrophages play essential roles in wound angiogenesis, coordinating both the initial blood vessel sprouting and subsequent vessel regression.